2021
DOI: 10.2147/ott.s297140
|View full text |Cite
|
Sign up to set email alerts
|

Tip of the Iceberg: Roles of CircRNAs in Cancer Glycolysis

Abstract: Warburg effect reflects that tumor cells tend to generate energy by aerobic glycolysis rather than oxidative phosphorylation (OXPHOS), thus promoting the development of malignant tumors. As a kind of non-coding RNA, circular RNA (circRNA) is characterized by a closed ring structure and emerges as a regulator of cancer metabolism. Mounting studies revealed that circRNA can regulate the cancer metabolism process through affecting the expression of glycolysis relevant enzymes, transcription factors (TFs), and sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 112 publications
0
9
0
1
Order By: Relevance
“…Targeting LDHA promotes DTX-induced cytotoxicity predominantly in castration-resistant PCa cells (37). Besides, several studies have revealed that circRNAs can regulate the cancer metabolism process by affecting the expression of glycolysis-relevant enzymes and pathways (38). In this study, we found that circARHGAP29 could promote LDHA-mediated cell proliferation and glycolysis in DTX-resistant PCa cells by binding to the IGF2BP2 protein.…”
Section: Discussionmentioning
confidence: 61%
“…Targeting LDHA promotes DTX-induced cytotoxicity predominantly in castration-resistant PCa cells (37). Besides, several studies have revealed that circRNAs can regulate the cancer metabolism process by affecting the expression of glycolysis-relevant enzymes and pathways (38). In this study, we found that circARHGAP29 could promote LDHA-mediated cell proliferation and glycolysis in DTX-resistant PCa cells by binding to the IGF2BP2 protein.…”
Section: Discussionmentioning
confidence: 61%
“…Compared with other lines, it is highly conservative. Most circular RNAs are abundant, stable, and conservative and often indicate tissue/developmental stage-specific patterns [ 22 ]. More circular RNA disorders are involved in several biological processes of malignant tumors, such as tumorigenesis, growth, invasion, metastasis, apoptosis, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Under physiological conditions, neurons mainly use most of the glucose to produce ATP through the pentose-phosphate pathway (PPP), while the glycolysis state is low [ 11 ]. When cerebral I/R occurs, neuronal glucose metabolism converts from PPP to glycolysis, which is induced by the increased expression of the glycolytic promoting enzymes such as lactate dehydrogenase A (LDHA), glucose transporter1 (GLUT1), and hexokinase2 (HK2) [ 11 , 12 ]. Enhancement of glycolysis also can lead to higher glucose consumption, more lactic acid accumulation, and less ATP production, which ultimately accelerates neuronal death [ 13 ].…”
Section: Introductionmentioning
confidence: 99%